2018
DOI: 10.1002/bjs.10724
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of metabolic surgery versus medical treatment for microvascular complications in patients with type 2 diabetes mellitus

Abstract: In patients with T2DM, metabolic surgery prevented the development of microvascular complications better than medical treatment . Metabolic surgery improved pre-existing diabetic nephropathy compared with medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 44 publications
(145 reference statements)
1
32
0
5
Order By: Relevance
“…The importance of operating earlier rather than later is further supported by the findings of the SOS study, which shows that metabolic surgery has a lower impact on the reduction of macro- and microvascular events the longer the T2DM existed prior to surgery [2,18]. In contrast, a recent meta-analysis did not find a relationship between the duration of T2DM and the efficacy of metabolic operations regarding the reduced incidence or improvement of microvascular complications [8]. Lastly, a recent study by Ahlqvist et al [20] found that there seem to be several subtypes of T2DM with different underlying causes such as high insulin resistance or insulin deficiency, and that these pose differing risks for the development of T2DM-related complications.…”
Section: Assessment Of Patients Suitable For Metabolic Surgerymentioning
confidence: 63%
See 4 more Smart Citations
“…The importance of operating earlier rather than later is further supported by the findings of the SOS study, which shows that metabolic surgery has a lower impact on the reduction of macro- and microvascular events the longer the T2DM existed prior to surgery [2,18]. In contrast, a recent meta-analysis did not find a relationship between the duration of T2DM and the efficacy of metabolic operations regarding the reduced incidence or improvement of microvascular complications [8]. Lastly, a recent study by Ahlqvist et al [20] found that there seem to be several subtypes of T2DM with different underlying causes such as high insulin resistance or insulin deficiency, and that these pose differing risks for the development of T2DM-related complications.…”
Section: Assessment Of Patients Suitable For Metabolic Surgerymentioning
confidence: 63%
“…Studies from our institution and others over the last few years have demonstrated that metabolic surgery, or the use of bariatric procedures to treat metabolic diseases, is an effective therapy for metabolic disease regardless of a patient's body weight/BMI. Furthermore, research demonstrates that metabolic surgical procedures also improve existing diabetic complications such as neuropathy and nephropathy [7,8,9,10]. In contrast to these findings, concerning non-severely obese patients with severe metabolic disease, there is also ample evidence that patients with a high degree of obesity can be metabolically healthy [11,12,13].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations